Efficacy of an accelerated double‐dose hepatitis B vaccine regimen in patients with cirrhosis. Issue 7 (1st April 2021) - Rodríguez‐Tajes, Sergio; Pocurull, Anna; Lens, Sabela; Mariño, Zoe; Olivas, Ignasi; Soy, Guillem; Alonso, Anna; Vilella, Anna; Forns, Xavier
Abstract: The hepatitis B (HBV) vaccine is recommended in unvaccinated adults with cirrhosis, despite its low efficacy. We aimed to evaluate the response to a double‐dose/accelerated vaccine schedule in patients with cirrhosis admitted into a hepatology ward. All patients with cirrhosis admitted to the hepatology ward without exclusion criteria were offered the HBV HBVAXPRO 40mcg vaccine at months 0, 1 and 2. Non‐responders received a second cycle. We evaluated 468 patients and only 19% were seroprotected against HBV. In 196 patients without exclusion criteria for HBV vaccination, the per protocol response rate (anti‐HBs >10 U/ml) was 23% after a first cycle and 59% after a second cycle. The overall response per intention to treat was only 23%. We have not identified predictors of response. Only one patient had a mild adverse event. Most patients with cirrhosis admitted in the hepatology ward are unprotected against HBV. Although a second HBV vaccination cycle increases the response rate, the poor overall response reinforces the implementation of HBV vaccination before the development of cirrhosis.